1985
DOI: 10.1002/art.1780280808
|View full text |Cite
|
Sign up to set email alerts
|

Anticytoskeletal autoantibodies in the connective tissue diseases

Abstract: The sera of 103 patients with connective tissue diseases were studied for the presence of anticytoskeletal antibodies by using an indirect immunofluorescence method. PTK2 cells fixed with paraformaldehyde and digitonin were used as substrate. Antibodies to intermediate filaments were detected in sera of 85.7% of polymyositis/dermatomyositis (PMIDM), 62.8% of systemic sclerosis, 54.5% of rheumatoid arthritis, and 37.5% of systemic lupus erythematosus patients, and in 42.5% of normal sera. High titers of these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 25 publications
(22 reference statements)
3
27
0
1
Order By: Relevance
“…Levels of anti-vimentin antibodies were previously shown to be significantly higher in patients with idiopathic pulmonary fibrosis and nonspecific interstitial pneumonia than in healthy controls (23). Vimentin has also been described as an autoantigen in rheumatic disease (14)(15)(16). Interestingly, it has been reported that pulmonary fibrosis is more common in RA patients who have anti-vimentin antibodies (24).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of anti-vimentin antibodies were previously shown to be significantly higher in patients with idiopathic pulmonary fibrosis and nonspecific interstitial pneumonia than in healthy controls (23). Vimentin has also been described as an autoantigen in rheumatic disease (14)(15)(16). Interestingly, it has been reported that pulmonary fibrosis is more common in RA patients who have anti-vimentin antibodies (24).…”
Section: Discussionmentioning
confidence: 99%
“…The neuronal cell intermediate filament or neurofilament is composed of 3 separate polypeptides of molecular weights 205, 160, and 70 kd (14,15). Studies indicating an increased incidence of antineurofilament antibodies (ANFA) in viral infections of the CNS (16) and in paraneoplastic neurologic disease (17,18), as well as recent work indicating an increased incidence of anticytoskeletal antibodies in connective tissue disease (19), have provided the primary focus of our study, which is to examine the occurrence and titer of ANFA in patients with NPSLE.…”
mentioning
confidence: 99%
“…Autoantibodies to centrioles and to centrosomes have also been described (39)(40)(41). In addition, we have previously reported in serum from a patient with CREST an autoantibody to the mitotic spindle poles and midbody (20,21). However further study of a larger group of patients will be required to determine if anti-MFAS is specific for systemic sclerosis.…”
Section: Discussionmentioning
confidence: 96%
“…We have used previously indirect immunofluorescence microscopy and immunoblot analysis to identify anticytoskeletal autoantibodies in human sera (6,(19)(20)(21) (17,22), who also provided chicken gizzard a-actinin and rabbit anti-beef heart a-actinin (13,23 Preparation ofcells, cytoskeletal extracts, and tissuesfor electrophoresis. PtK2 cells were washed with phosphate-buffered saline (PBS) containing a mixture of protease inhibitors (2.5 mg/ml leupeptin, 2.5 mg/ml aprotinin, 100 mM benzamidine, 50 mM phenylmethylsulfonyl fluoride [PMSF], and 1.0 mg/ml pepstatin) diluted 100-fold (25).…”
Section: Introductionmentioning
confidence: 99%